KARAKTERISASI SOSIS DAGING AYAM YANG DIBUAT DENGAN PENAMBAHAN TEPUNG KOMPOSIT TAPIOKA DAN GEMBOLO SEBAGAI BAHAN PENGISI - . Herlina; Niken Widya Palupi; Akbar Nur Bani Rusmana (JURNAL AGROTEKNOLOGI, 2012)
The gembolo contains glucomannan and has the ability to WHC 1900%. To extend the shelf life of the gembolo can be made into flour. To prevent browning reactions by enzymes that do steam blanching. Gembolo flour can be used as composite flour in the manufacture of sausages, which are used for filler than tapioca. The objectives of the experiment were to evaluate physical, chemical, and sensory characteristics of chicken sausage bydifferent types and concentrations of composite gembolo flour. The study uses two factors, the first factor is types of gembolo flour (gembolo flour natural and gembolo flour with blanching) and the second is the concentration of gembolo flour (10%, 20%, and 30%). Each treatment was repeated 5 times. Test data of physical and chemical characteristics were analyzed by analysis of variance, if different tested with Duncan's New Multiple Range Test. Sausage oranoleptik test data were analyzed by Friedman test. Appropriate treatmenttoproducechicken sausage with the best physical and preferred isA2B1withtypes gembolo flour with blansing concentration of gembolo flour 10%. The chicken sausage has a value ofWHC 85,33%, value oftexture 45,50 g/mm, brightnessvalue 46,11, cooking loss 5,21%, water content 63,69%, protein content 14,99%, ash content 0,68%, fat content 2,04%, carbohydrate 18,60%.Keywords: meat chicken sausage, composite, tapioca, gembolo, filler